2017
DOI: 10.1016/j.solmat.2017.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic properties of thin film Cu2ZnGeSe4 solar cells

Abstract: The fabrication and properties of a Ge-based Kesterite Cu2ZnGeSe4 (CZGSe)solar cell are discussed. The existence of the quaternary compound has been verified by physical methods such as X Ray Diffraction (XRD) and Energy Dispersive Spectroscopy (EDS). The Cu2ZnGeSe4 solar cell has a power conversion efficiency (PCE) of 5.5% under AM1.5G illumination which is among the highest reported for pure Ge substitution. Detailed low temperature current-voltage and time-resolved photoluminescence measurements show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…In this series, the lowest V OC deficit of 868 mV could be obtained with 5 mg of GeS. However, this value is still much higher than for the most efficient CZTSSe absorber (617 mV [27]) and higher than the deficit of 656 mV that can be obtained for a CZGSe absorber with a band gap of 1.4 eV [4]. As band gap increases, the V OC deficit increases to values larger than 1 V, thereby drastically limiting the photovoltaic performance.…”
Section: Higher [S]/([s] + [Se])mentioning
confidence: 56%
See 1 more Smart Citation
“…In this series, the lowest V OC deficit of 868 mV could be obtained with 5 mg of GeS. However, this value is still much higher than for the most efficient CZTSSe absorber (617 mV [27]) and higher than the deficit of 656 mV that can be obtained for a CZGSe absorber with a band gap of 1.4 eV [4]. As band gap increases, the V OC deficit increases to values larger than 1 V, thereby drastically limiting the photovoltaic performance.…”
Section: Higher [S]/([s] + [Se])mentioning
confidence: 56%
“…Its similarity to the extensively studied Cu 2 ZnSnS x Se 4-x (CZTSSe) offers potential for fast progress in the improvement of material properties and solar cell efficiency, with a record value of 6.0% so far [3]. However, the band gaps in previous publications are in a range between 1.4 eV [4] and 1.5 eV [5] and are therefore still too low for application as top cells in multijunction solar cells.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, the full range of Ge substitution has been investigated to some extent, including the pure Ge compound in recent reports, demonstrating that the CZGSe exhibits also kesterite structure [123]. Among the most relevant pure Ge kesterite results, Schnabel et al reported efficiencies exceeding 5% for a sulfo-selenide CZGSSe (E g ∌1.5 eV) solar cell [124], while for the selenide CZGSe (Eg∌1.4 eV) compound, Sahayaraj et al published a 5.5% efficiency device with a remarkable V OC of 744 mV [125]. Intriguingly, the Ge based kesterite showed less electrical losses from band tailing/electrostatic potential fluctuations compared to Ge free devices [125,126].…”
Section: Germanium (Ge)mentioning
confidence: 99%
“…The origin of these low efficiencies can be mainly attributed to a limited VOC, which never surpasses 65% of SQ limit whereas FF and JSC can reach up to 80% of this limit. Introduction of Ge in CZTGSe absorbers has been claimed to improve devices properties and particularly VOC [22][23][24][25][26] but Ge containing devices currently do not outperform their Ge-free counterparts in literature. At low Ge content, FF and VOC are similar to Ge-free CZTSSe solar cells but with lower JSC while at higher content, an additional drop in FF is noticed.…”
Section: Mapping Of Fundamental Failures In Cd-free Kesterite Solar Cmentioning
confidence: 99%
“…12 . PV data and related bandgaps from References [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] . Bandgaps are extracted from EQE spectra.…”
Section: Mapping Of Fundamental Failures In Cd-free Kesterite Solar Cmentioning
confidence: 99%